2012
DOI: 10.1002/anie.201208554
|View full text |Cite
|
Sign up to set email alerts
|

A Generic One‐Pot Route to Acyclic Two‐Coordinate Silylenes from Silicon(IV) Precursors: Synthesis and Structural Characterization of a Silylsilylene

Abstract: Si in sight: a one-pot, single-step synthesis of an acyclic silylsilylene, Si{Si(SiMe(3))(3)}{N(SiMe(3))Dipp} (Dipp=2,6-iPr(2)C(6)H(3)), from a silicon(IV) starting material is reported, together with evidence for a mechanism involving alkali metal silylenoid intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 62 publications
5
101
1
5
Order By: Relevance
“…The first reports of isolable silylenes belonging to this class only appeared very recently (for a recent perspective, see: [84]) and was simultaneously reported by Power and co-workers [85] and the groups of Jones, Mountford, Aldridge and Kaltsoyannis [86]. Power's approach employs reduction of the Si(IV) precursor SiBr 2 (SAr Even more recently, Jones, Mountford, Aldridge and Kaltsoyannis and co-workers reported a one-pot synthetic route to accessing a silyl-substituted two-coordinate acyclic silylene :Si{N(Dipp)(tms)}{Si(SiMe 3 ) 3 } (100) [88] obtained by facile reduction of the Si(IV) precursor SiBr 3 {N(Dipp)(tms)} (102) with (thf) 2 K[Si(SiMe 3 ) 3 ] which afforded 100. Noteworthy is that attempted reduction of 102 with the standard reducing agent KC 8 afforded the dinuclear species {N(Dipp)(tms)}SiBr 2 -Br 2 Si{N(Dipp)(tms)} (103).…”
Section: Shmentioning
confidence: 99%
“…The first reports of isolable silylenes belonging to this class only appeared very recently (for a recent perspective, see: [84]) and was simultaneously reported by Power and co-workers [85] and the groups of Jones, Mountford, Aldridge and Kaltsoyannis [86]. Power's approach employs reduction of the Si(IV) precursor SiBr 2 (SAr Even more recently, Jones, Mountford, Aldridge and Kaltsoyannis and co-workers reported a one-pot synthetic route to accessing a silyl-substituted two-coordinate acyclic silylene :Si{N(Dipp)(tms)}{Si(SiMe 3 ) 3 } (100) [88] obtained by facile reduction of the Si(IV) precursor SiBr 3 {N(Dipp)(tms)} (102) with (thf) 2 K[Si(SiMe 3 ) 3 ] which afforded 100. Noteworthy is that attempted reduction of 102 with the standard reducing agent KC 8 afforded the dinuclear species {N(Dipp)(tms)}SiBr 2 -Br 2 Si{N(Dipp)(tms)} (103).…”
Section: Shmentioning
confidence: 99%
“…The 29 Si NMR resonance of 1 is observed at d = 13.3 ppm, akin to the value observed for an ocarborane bridged bis-NHSi ligand. [13] With 1 in hand we investigated its reactivity towards dioxygen. Thecalculations revealed that the HOMO is largely localized at the Si II center, featuring significant 3s (31.59 %) and 3p character (36.48 %), while the LUMO has mainly boron 2p character (41.94 %, see FigureS6 in the Supporting Information).…”
mentioning
confidence: 99%
“…Indeed, besides FLP, a few main group compounds have been shown to split H 2 at a unique reactive site. [16] Bertrand et al pioneered the field with ambiphilic acyclic and cyclic amino carbenes, [17] Aldridge and co-workers generalized the approach to aminoboryl and aminosilyl silylenes, [18] and Piers et al extended the field to highly electron-deficient antiaromatic boroles [2a] (see Refs. [19,20] for additional examples).…”
mentioning
confidence: 99%